Correlation between methylation of the caveolin‐1 gene and of caveolin‐1 messenger ribonucleic acid, and protein levels and human epidermal growth factor receptor 2 protein expression in adenocarcinomas of the esophagogastric junction. Issue Volume 3:Issues 1(2019) (25th February 2019) - Liu, Ruizhen; Kong, Yi; Sun, Pengbo; Li, Faliang; Shi, Xiaopeng
Abstract: Objective: To investigate the methylation level of caveolin‐1 gene (CAV1) in human adenocarcinomas of the esophagogastric junction (AEG) and distal normal tissues (>10 cm from cancerous foci), and to study the protein expression level of CAV1 and human epidermal growth factor receptor 2 (Her‐2) in AEG and their relationship with CAV1 methylation. Methods: Methylation‐specific polymerase chain reaction was used to detect the methylation level of CAV1 in 67 cases with AEG and distal normal tissues. The mRNA level of CAV1 in AEG and distal normal tissues was detected by reverse transcription polymerase chain reaction. Immunohistochemistry was used to detect the protein expression levels of CAV1 and Her‐2. The correlation between CAV1 methylation, CAV1 mRNA level, CAV1 protein, and Her‐2 protein was further analyzed. Results: In AEG, the methylation rate of CAV1 was 28.4% (19/67), and almost no methylation of this gene was found in the distal normal tissues ( P < 0.01). The methylation level of CAV1 in carcinoma tissues was related to tumor size, differentiation, and lymph node metastasis in patients ( P < 0.05), but was not related to sex, age, the presence of vascular carcinoma thrombus, and clinical stages. The expression rate of CAV1 mRNA and protein in carcinoma tissues was 46.3% and 41.8%, respectively, which was dramatically lower than that in distal normal tissues ( P < 0.01). The protein expression level of CAV1 and Her‐2 in carcinoma tissues was correlated with the CAV1 methylation level ( P < 0.05). Conclusions: Methylation of CAV1 might be involved in tumor development, and associated with the mRNA and protein expression of CAV1 and Her‐2 protein expression in AEG, which could play an important role in the formation and progression of AEG.